Appendix 5.12: UP ROTC Website Profile on Alumnus Ferdinand E. Marcos - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Precisely who wrote this brief biographical note of “master politician” Ferdinand E. Marcos is unknown. Exactly the same note appears in the Department of National Defense website (www.dnd.gov.ph/ferdinand-marcos.html), where he is featured because he twice headed the department while concurrently serving as president. Based on webpage copies cached via the Internet Archive’s Wayback Machine, the UP ROTC posted the profile first; the earliest of those copies is shown here. In any case, that a laudatory biography of Marcos appears in two websites concerned with national defense and security in this decade shows Marcos’s continuing hold within communities that were instrumental to the enforcement of the dictatorship.